Música popular maranhense e a questão da identidade cultural regional - SANTOS, Ricarte Almeida (2012)
The work seeks to investigate the appearance and the development of a modern popular music produced in the state of Maranhão, starting with the incorporation of symbols and elements from popular culture by the music of composers from this referred state, in the mid of the 1970 s, and is later forthcoming with the tools of the cultural industry in the political context of Maranhão. The recording of the LP Bandeira de Aço , by Papete, in 1978, gathering compositions from Cesar Texeira, Josias Sobrinho, Sérgio Habibe (and Ronaldo Mota) assured that a large visibility was given to the rising popular music and started to generate a better acceptance from society of that new musical aesthetics and the expression of popular culture. The analysis contained in the present work are theoretically based on Thompson and Geertz, mainly, and also aims to analyze the expansion of the phenomena as from the onset of Mirante FM radio station, in the 1980 s, and the relation of that production with the cultural and political industry.